Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3109/08830185.2011.569903
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Protein 17: Clinical Relevance of a Cancer/Testis Antigen, from Contraception to Cancer Immunotherapy, and Beyond

Abstract: Sperm protein 17 belongs to the cancer/testis antigen family and was found to play a key role in the cell fusion process between the mammalian spermatozoa and egg. Sperm protein 17-specific autoantibodies in vasectomized males suggest its high expression in the testis. Sperm protein 17 expression levels are low or absent in normal tissues, other than the testis. Sperm protein 17 is expressed by tumors, including ovarian cancer, indicating that it is an ideal target for cancer immunotherapy, and plays a role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 69 publications
(123 reference statements)
0
11
0
Order By: Relevance
“…Figure shows that the splenocytes from placebo‐treated mice contained SP17 specific T‐cells, although at a lower frequency compared with those from the vaccine group. This was expected, since it was shown that, being SP17 a highly immunogenic antigen, spontaneous SP17‐specific responses can arise in vivo and such pre‐existing SP17‐specific T cells can be stimulated ex vivo, although in the absence of a vaccination strategy such the one we tested here, they are likely inefficient in controlling the growth of malignant cells.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Figure shows that the splenocytes from placebo‐treated mice contained SP17 specific T‐cells, although at a lower frequency compared with those from the vaccine group. This was expected, since it was shown that, being SP17 a highly immunogenic antigen, spontaneous SP17‐specific responses can arise in vivo and such pre‐existing SP17‐specific T cells can be stimulated ex vivo, although in the absence of a vaccination strategy such the one we tested here, they are likely inefficient in controlling the growth of malignant cells.…”
Section: Discussionmentioning
confidence: 73%
“…Due to this tumor‐restricted pattern of expression combined with their strong in vivo immunogenicity, CTAs represent ideal targets for tumor‐specific immunotherapeutic strategies. As an example, the small (17.4 kDa) antigenic CTA, sperm protein 17 (SP17), highly expressed in spermatozoa and largely conserved between mouse and human (94% homology), is aberrantly expressed in multiple cancers of unrelated histological origins, including OC, multiple myeloma (MM), nervous system tumors, as well as lung and esophageal cancers, among others . Our work has previously demonstrated that SP17‐specific CD8+ cytotoxic T lymphocytes (CTL) are capable to kill MM cells presenting SP17 epitopes on major histocompatibility complex (MHC) class I molecules .…”
Section: Introductionmentioning
confidence: 99%
“…Here, we propose a different model in which Notch signaling and CTA expression interact to maintain a self-replicating MM cell population. Although CTA expression has been described in a broad range of solid and hematologic malignancies [33,35,36,39,40,41,43], MM is distinct in that a significant majority of patients express AKAP-4 and/or SP17 in their tumor cells [34,37,38,42]. No other type of cancer has such a close association with specific CTA expression pattern.…”
Section: Interactions Between Notch Signaling and Cta Expression In Tmentioning
confidence: 99%
“…Several investigators have since demonstrated that various malignant tumors of unrelated histological origin express Sp17, including multiple myeloma [14], ovarian cancer [15][16][17][18][19][20], esophageal squamous cell carcinomas [21], endometrial and cervical cancers [22], esthesioneuroblastomas [23], and several other subtypes of human nervous system tumors [24]. Some authors have proposed that the role of Sp17 in transformed cells is to promote cell-to-cell and cell-to-matrix adhesion, in this way contributing to motility and migration in cancer cells [25,26].…”
mentioning
confidence: 99%